1998
DOI: 10.1159/000024499
|View full text |Cite
|
Sign up to set email alerts
|

Invasion Strategies of the Oral Pathogen <i>Porphyromonas gingivalis:</i> Implications for Cardiovascular Disease

Abstract: Microorganisms have evolved a variety of mechanisms designed to evade detection and/or destruction by the host. Many pathogens evade host defenses by invading cells, thus providing the bacterium with an environment free of competing microorganisms. Adherence and invasion are active processes in which microorganisms often use host proteins and enzymes to gain entry into the cell, thus stimulating their own uptake. The investigation of invasion by the periopathogen Porphyromonas gingivalis is in its infancy in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 29 publications
1
62
0
3
Order By: Relevance
“…Evidence for definitive molecular mechanisms underlying these observations are being uncovered, as studies in vitro suggest that P gingivalis can invade primary cultures of human coronary artery endothelial cells. 34,35 These observations suggest that once these bacteria adhere to and invade endothelial cells, they may directly activate signal transduction pathways linked to the proinflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for definitive molecular mechanisms underlying these observations are being uncovered, as studies in vitro suggest that P gingivalis can invade primary cultures of human coronary artery endothelial cells. 34,35 These observations suggest that once these bacteria adhere to and invade endothelial cells, they may directly activate signal transduction pathways linked to the proinflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize again, however, that evidence linking P gingivalis specifically to vascular/inflammatory cell perturbation is already emerging. [32][33][34][35][36] Pilot studies from our group have shown that P gingivalis infection of human monocytes incubated with LDL significantly increased foam cell formation compared with LDL incubation alone. DPG3, the fimbriae-deficient mutant of P gingivalis that lacks the ability to adhere to and invade host cells, an important determinant of its pathogenicity in human periodontitis, did not have such an effect.…”
Section: Discussionmentioning
confidence: 99%
“…18,21,[43][44][45] In gingival epithelial cells (GEC), P. gingivalis accumulates in the perinuclear area and neither apoptosis nor necrotic cell death is observed. 43,46,47 However, in KB cells the bacteria are found free in the cytosol or within single-membrane bound vacuoles.…”
Section: Bacterial Persistence and Host Cell Survivalmentioning
confidence: 99%
“…These inflammatory molecules have demonstrated significant roles in the initiation and/or acceleration of atherosclerosis. Recent studies have established that P. gingivalis invasion of endothelial cells from various tissues (fetal bovine heart, bovine aorta, and human umbilical vein) is dependent on bacterial fimbriae, as is activation of endothelial responses (9,(33)(34)(35). Furthermore, adherence and invasion of the corresponding FimA mutant DPG3, which lacks the major fimbriae, were not detected (9, 33).…”
Section: Discussionmentioning
confidence: 99%